Mapping Disaster Hazards and Risks – A Case Study in Kuala Lumpur City (KLC) - Ahmad Najman; Azam Zul Bahari; Choy Peng Ng; Mohd. Muhaimin Ridwan Wong; Muhamad Faisharulfaizi Mohd Rofi; Nordila Ahmad; Fuad Abas; Teik Hua Law (Penerbit Universiti Kebangsaan Malaysia, 2025)
Kuala Lumpur, the capital city of Malaysia, is vulnerable to various natural and man-made disasters. Kuala Lumpur